Features of the fetoplacental unit functional state in pregnant women with Epstein-Barr virus infection - A. Yu. Pekar; R. M. Mitsoda (Zaporožskij Medicinskij Žurnal)
Epstein-Barr virus (EBV) high prevalence, variety of its pathways, effects on gestational process, clear criteria of EBV infection diagnostics in pregnant women lack indicated study problem actuality.